Repeat testing of low-level HIV-1 RNA: assay performance and implementation in clinical trials. (15th May 2018) - White, Kirsten; Garner, Will; Wei, Lilian; Eron, Joseph J.; Zhong, Lijie; Miller, Michael D.; Martin, Hal; Plummer, Andrew; Tran-Muchowski, Cecilia; Lindstrom, Kim; Porter, James; Piontkowsky, David; et al.
Abstract : Objective: Assess the performance of HIV-1 RNA repeat testing of stored samples in cases of low-level viremia during clinical trials. Design: Prospective and retrospective analysis of randomized clinical trial samples and reference standards. Methods: To evaluate assay variability of the Cobas AmpliPrep/Cobas TaqMan HIV-1 Test, v2.0, three separate sources of samples were utilized: the World Health Organization (WHO) HIV reference standard (assayed using 50 independent measurements at six viral loads <200 copies/ml), retrospective analysis of four to six aliquots of plasma samples from four clinical trial participants, and prospective repeat testing of 120 samples from participants in randomized trials with low-level viremia. Results: The TaqMan assay on the WHO HIV-1 RNA standards at viral loads <200 copies/ml performed within the expected variability according to assay specifications. However, standards with low viral loads of 36 and 18 copies/ml reported values of ≥ 50 copies/ml in 66 and 18% of tests, respectively. In participants treated with antiretrovirals who had unexpected viremia of 50–200 copies/ml after achieving <50 copies/ml, retesting of multiple aliquots of stored plasma found <50 copies/ml in nearly all cases upon retesting (14/15; 93%). Repeat testing was prospectively implemented in four clinical trials for all samples with virologic rebound of 50–200 copies/ml ( n = 120 samples from 92 participants) from which 42% (50/120) had a retest result of less than 50 copies/ml and 58% (70/120) retested ≥ 50 copies/ml. Conclusion: The TaqMan HIV-1 RNA assay shows variability around 50 copies/ml that affects clinical trial results and may impact clinical practice. In participants with a history of viral load suppression, unexpected low-level viremia may be because of assay variability rather than low drug adherence or true virologic failure. Retesting a stored aliquot of the same sample may differentiate between assay variability and virologic failure as the source of viremia. This retesting strategy could save time, money, and anxiety for patients and their providers, as well as decrease follow-up clinic visits without increasing the risk of virologic failure and resistance development.